2021
DOI: 10.4049/immunohorizons.2100059
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Cell Death, PANoptosis, Mediated by Cytokines in Diverse Cancer Lineages Inhibits Tumor Growth

Abstract: Resistance to cell death is a hallmark of cancer. Immunotherapy, particularly immune checkpoint blockade therapy, drives immunemediated cell death and has greatly improved treatment outcomes for some patients with cancer, but it often fails clinically. Its success relies on the cytokines and cytotoxic functions of effector immune cells to bypass the resistance to cell death and eliminate cancer cells. However, the specific cytokines capable of inducing cell death in tumors and the mechanisms that connect cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
94
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 123 publications
(113 citation statements)
references
References 98 publications
0
94
1
Order By: Relevance
“…In addition to inflammation, dysregulation of or acquired resistance to cell death can regulate tumorigenesis. The IFN signaling pathway is known to be important in this process; for example, IRF1 acts as a tumor suppressor in a mouse model of CRC and in human cancer cells by promoting PANoptosis [ 21 , 22 ]. PANoptosis is an innate immune inflammatory programmed cell death pathway dependent on PANoptosomes, caspase(s)-containing complexes with or without inflammasome components and RHIM-containing proteins [ 15 , 21 , 22 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to inflammation, dysregulation of or acquired resistance to cell death can regulate tumorigenesis. The IFN signaling pathway is known to be important in this process; for example, IRF1 acts as a tumor suppressor in a mouse model of CRC and in human cancer cells by promoting PANoptosis [ 21 , 22 ]. PANoptosis is an innate immune inflammatory programmed cell death pathway dependent on PANoptosomes, caspase(s)-containing complexes with or without inflammasome components and RHIM-containing proteins [ 15 , 21 , 22 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the azoxymethane (AOM)/dextran sodium sulfate (DSS)-induced mouse model of CRC, IRF3-deficient mice develop more tumors [ 19 ], while type I IFN receptor (IFNAR)-deficient mice develop a similar number of tumors when compared with WT mice [ 20 ]. Additionally, we recently reported the tumor suppressive function of IRF1 during CRC, as IRF1 potentiates inflammatory cell death, PANoptosis, in cancer cells [ 21 , 22 ]. STAT1 and STAT2, two of the key components of the ISGF3 complex that regulates the production of many ISGs, are also reported to have distinctive functions in CRC [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…RIPK3-mediated oligomerization of MLKL produces necroptosis [87][88][89]. Pyroptosis and necroptosis are lytic death processes in which cytokines and other cellular components are released [85,[89][90][91].…”
Section: Panoptosismentioning
confidence: 99%
“…Recent studies have found extensive crosstalk between programmed cell death pathways, establishing the concept of PANoptosis (pyroptosis, apoptosis, necroptosis) (Gurung et al, 2014;Kuriakose et al, 2016;Lamkanfi et al, 2008;Lee et al, 2020Lee et al, , 2021bMalireddi et al, 2010Malireddi et al, , 2021Place et al, 2021). Although inflammasome activation is primarily associated with gasdermin D (GSDMD)-mediated pyroptosis, there is emerging evidence of the contribution of inflammasome components in driving PANoptosis (Christgen et al, 2020;Gurung et al, 2014;Kesavardhana et al, 2020;Kuriakose et al, 2016;Lee et al, 2020Lee et al, , 2021bMalireddi et al, 2020Malireddi et al, , 2021Place et al, 2021;Zheng et al, 2020).…”
Section: Apoptosis In Alzheimer's Diseasementioning
confidence: 99%